Salivary gland involvement in granulomatosis with polyangiitis: Case report and review of literature - Kunal Chandwar; Kriti Kishor; Sayan Mukherjee; Urmila Dhakad (Indian Journal of Rheumatology)
We present a case of granulomatosis with polyangiitis (GPA) presenting with salivary gland enlargement and right parotid abscess, left-sided facial palsy, Lacrimal Gland, extraocular muscle involvement and rapidly progressive necrotizing keratitis. Followed by review of available literature on salivary gland involvement in GPA and how salivary gland involvement may be a good prognostic factor with less renal and central nervous system involvement and argue for greater vigilance in diagnosing salivary gland involvement in GPA. An approach to a patient with salivary gland involvement and suspected autoimmune disease wtih Sjögren's Syndrome, IgG4 disease,Antineutrophil cytoplasmic antibodies (ANCA) associated vasculitis and Sarcoidosis is discussed.